2020
DOI: 10.1111/ajt.15749
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation and chronic disease management: Moving beyond patient and graft survival

Abstract: A paradigm shift is needed, whereby care provided by liver transplant centers needs to focus not only on survival but also on optimizing long‐term management and overall health of liver transplant recipients. VanWagner et al’s article is on page 797.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Although not unique to CVD care, this system-level failure points to the need for a redesign of the systems and processes of CVD care and potentially of other chronic disease management in LTRs. (19)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not unique to CVD care, this system-level failure points to the need for a redesign of the systems and processes of CVD care and potentially of other chronic disease management in LTRs. (19)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the capacity to provide longterm care for LTRs is an issue due to the number of LTRs increasing in the United States with prolonged patient and graft survival, and aging of the LTR population who now more closely resemble a general chronic disease population. (18,19) LT providers indicated that they are no longer able to provide adequate CVD care to all LTRs because of time constraints and competing health priorities (ie, immunosuppression management). Personalized care planning, used often with medically complex patients, may be a potential system-based solution to improving CVD outcomes in LTRs.…”
Section: Discussionmentioning
confidence: 99%
“…29 Admittedly, designing a CIM intervention will require adapted methods beyond the traditional clinical research methods to achieve successful implementation, adoption, and sustainability of an innovative model of care for follow-up of transplant patients. 30 Implementation science could offer a way forward to achieve success in this regard. 31 We are currently investing in developing, implementing, and testing this CIM-based eHealth-powered integrated care modelconsisting of a human-component (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing consensus in the transplant community that quality metrics and quality improvement should also consider longer‐term survival and patient‐centered and clinically relevant outcomes. ( 29,30 ) Patients who pursue LT inherently expect improvements in quality of life without significant comorbid disease, but this is not always the case. ( 1,8 ) Understanding center‐specific variation with regard to health care utilization and relevant comorbidities may allow for internal assessment of referral processes, patient selection, WL management, and posttransplant care.…”
Section: Discussionmentioning
confidence: 99%